An updated classification of the Brassicaceae (Cruciferae) - German, Dmitry; Hendriks, Kasper P.; Koch, Marcus; Lens, Frederic; Lysak, Martin A.; Bailey, C. Donovan; Mummenhoff, Klaus; Al-Shehbaz, Ihsan A. (PhytoKeys, 2023)
Based on recent achievements in phylogenetic studies of the Brassicaceae, a novel infrafamilial classification is proposed that includes major improvements at the subfamilial and supertribal levels. Herein, the family is subdivided into two subfamilies, Aethionemoideae (subfam. nov.) and Brassicoideae. The Brassicoideae, with 57 of the 58 tribes of Brassicaceae, are further partitioned into five supertribes, including the previously recognized Brassicodae and the newly established Arabodae, Camelinodae, Heliophilodae, and Hesperodae. Additional tribus-level contributions include descriptions of the newly recognized Arabidopsideae, Asperuginoideae, Hemilophieae, Schrenkielleae, and resurrection of the Chamireae and Subularieae. Further detailed comments on 17 tribes in need of clarifications are provided.
Gesehen am 12.12.2023